Ferric oxide nanocatalyst: synthesis, characterization, and application in the one-pot three-component synthesis of 3,4,5-trisubstituted isoxazole derivatives - Totre, Ganesh; Shinde, Dnyaneshwar; Shirsath, Sachin; Patil, Prakash; Kulkarni, Pramod (Monatshefte Fur Chemie, 2024)
In this study, we have focused on the preparation and application of a nano-ferric oxide catalyst as a heterogeneous catalyst in the one-pot, three-component synthesis of isoxazole derivatives. The ferric oxide catalyst was synthesized using a simple precipitation method and thoroughly characterized using techniques such as FT-IR, XRD, SEM, EDX, and BET. The effectiveness of the ferric oxide catalyst as a heterogeneous catalyst was investigated in the synthesis of 3,4,5-trisubstituted isoxazole. The results of the synthesis demonstrated that the catalyst exhibited high efficiency in facilitating the three-component, one-pot synthesis of 3,4,5-trisubstituted isoxazole derivatives. The synthesis route employed in this study offers several advantages, including its simplicity, ease of workup, and environmental friendliness. Furthermore, the catalyst was successfully recovered and reused for five cycles without experiencing a significant loss in catalytic activity. This finding highlights the excellent stability and promising potential of the catalyst for organic transformations. Overall, our study showcases the successful preparation and application of the nano-ferric oxide catalyst in the synthesis of isoxazole derivatives, providing valuable insights into its catalytic performance and potential for future applications in organic chemistry.
Keywords: Ferric oxide nanoparticles; heterogeneous catalyst; Isoxazole; Multicomponent reaction